2007
DOI: 10.1242/jeb.003897
|View full text |Cite
|
Sign up to set email alerts
|

Allometric scaling in centrarchid fish: origins of intra- and inter-specific variation in oxidative and glycolytic enzyme levels in muscle

Abstract: glycolytic enzyme pyruvate kinase (PK) showed positive scaling, with scaling coefficients ranging from +0.08 to +0.23. The ratio of mass-specific enzyme activity in PK to CS increased with body size, whereas the ratio of mRNA transcripts of PK to CS was unaffected, suggesting the enzyme relationships were not due simply to transcriptional regulation of both genes. The massdependent differences in PK activities were best explained by transcriptional regulation of the muscle PK gene; PK mRNA was a good predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 33 publications
3
33
0
2
Order By: Relevance
“…Somero and Childress (36) were the first to note the reciprocal pattern in scaling of mitochondrial and glycolytic enzymes, the same relationship observed in our study and others (10,15). It is unclear whether this pattern arises as a result of independent regulatory pathways or a single pathway with reciprocal effects.…”
Section: Reciprocal Regulation Of Oxphos and Glycolytic Genessupporting
confidence: 80%
See 1 more Smart Citation
“…Somero and Childress (36) were the first to note the reciprocal pattern in scaling of mitochondrial and glycolytic enzymes, the same relationship observed in our study and others (10,15). It is unclear whether this pattern arises as a result of independent regulatory pathways or a single pathway with reciprocal effects.…”
Section: Reciprocal Regulation Of Oxphos and Glycolytic Genessupporting
confidence: 80%
“…Thus, consideration of myonuclear content reduced the differences between muscles of a species, but not differences between species. Previous studies with fish reached the same conclusion: expressing mitochondrial enzyme activities relative to DNA content largely negated differences in mitochondrial enzymes in relation to size (10) and between fibers (8) but did not affect differences between species (8).…”
Section: Scaling Of Metabolic Enzyme Activitiesmentioning
confidence: 60%
“…Subsequent studies have confirmed this general pattern, although interspecific differences are influenced by life history, activity levels and Integrated muscle response to growth phylogenetic relationships (Childress and Somero, 1990). Hence, LDH and PK showed positive allometry (b>0) in white muscle of many fishes (Burness et al, 1999;Davies and Moyes, 2007;Ewart et al, 1988;Martinez et al, 2000;Sullivan and Somero, 1983;Torres and Somero, 1988), whereas in striped bass positive scaling was found in small and medium, but not large (>1000g) fish (Norton et al, 2000). The same trend was also demonstrated in the present study in which LDH scaled with a similar exponent (b0.342) to that previously reported (b0.31) (Norton et al, 2000), although PK had weaker positive allometry (b0.110 and b0.56, respectively).…”
Section: Metabolismmentioning
confidence: 83%
“…Importantly, CPK also displayed positive allometry in trout white muscle (Burness et al, 1999) and in the present study, where the scaling exponent showed the strongest positive allometry (P<0.0001). By contrast, the oxidative enzymes COX and CS displayed negative allometry in fish white muscle (Davies and Moyes, 2007;Martinez et al, 2000;Torres and Somero, 1988;Tripathi and Verma, 2004). However, CS displayed no size dependence in other species (Burness et al, 1999;Torres and Somero, 1988).…”
Section: Metabolismmentioning
confidence: 90%
“…Thus, standard ANCOVAs are still commonly used in scaling studies (e.g. Niven and Scharlemann, 2005;Davies and Moyes, 2007;Snelling et al, 2011;Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%